2022
DOI: 10.1186/s13018-022-02929-5
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral biportal endoscopic discectomy versus percutaneous endoscopic lumbar discectomy in the treatment of lumbar disc herniation: a retrospective study

Abstract: Background Unilateral biportal endoscopic discectomy (UBE) is a rapidly growing surgical method that uses arthroscopic system for treatment of lumbar disc herniation (LDH), while percutaneous endoscopic lumbar discectomy (PELD) has been standardized as a representative minimally invasive spine surgical technique for LDH. The purpose of this study was to compare the clinical outcomes between UBE and PELD for treatment of patients with LDH. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 30 publications
3
51
0
1
Order By: Relevance
“…Three studies [ 16 18 ] reported preoperative VAS of back pain between UBE and PELD (134 patients, 64 in the UBE group and 70 in the PELD group). Meta-analysis showed no statistically significant difference in preoperative VAS of back pain between the two groups (WMD = −0.24, 95% CI (-0.57, 0.10), P = 0.16, heterogeneity: Tau 2 = 0.00, χ 2 = 0.00, df = 2 ( P = 1.00), I 2 = 0%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies [ 16 18 ] reported preoperative VAS of back pain between UBE and PELD (134 patients, 64 in the UBE group and 70 in the PELD group). Meta-analysis showed no statistically significant difference in preoperative VAS of back pain between the two groups (WMD = −0.24, 95% CI (-0.57, 0.10), P = 0.16, heterogeneity: Tau 2 = 0.00, χ 2 = 0.00, df = 2 ( P = 1.00), I 2 = 0%).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [ 16 18 ] reported VAS of leg pain between UBE and PELD preoperatively, 3 days postoperatively, and 30 days postoperatively (134 patients, 64 in the UBED group and 70 in the PELD group). Meta-analysis showed that the difference in VAS of leg pain between the two groups preoperatively was not statistically significant (WMD = −0.10, 95% CI (-0.42, 0.22), P = 0.54, heterogeneity: Tau 2 = 0.00, χ 2 = 0.54, df = 2 ( P = 0.76), I 2 = 0%); the difference in VAS of leg pain at postoperative 3 days was not statistically significant (WMD = 0.21, 95% CI (-0.20, 0.61), P = 0.33, heterogeneity: χ 2 = 0.08, df = 1 ( P = 0.77), I 2 = 0%); the difference in VAS of leg pain at 30 days postoperatively was not statistically significant (WMD = 0.09, 95% CI (-0.29, 0.46), P = 0.65, heterogeneity: Tau 2 = 0.04, χ 2 = 2.96, df = 2 ( P = 0.23), I 2 = 32%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study selection flow chart is shown in Figure 1. The 16 eligible articles (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) included 19 comparison groups, with a combined 653 patients who underwent UBE, 612 who underwent MED, 153 who underwent PELD, and 70 who underwent PLIF. Of the 16 included articles, 2 were RCTs, 5 were cohort studies, and 9 were case-control studies.…”
Section: Study Selectionmentioning
confidence: 99%